"Hand-Me-Down Habitats": Bicycles, Youth, and Open Space in the 1970s. Issue 1 (1st December 2022) - Frehner, Brian
Abstract: During the 1970s, young boys rode their bicycles more frequently and in greater numbers than at any other time in the United States' past. Bicycle riding and racing became so popular in the 1970s that boys fashioned a culture of BMX, also known as bicycle motocross. The style of bicycles and riding that BMXers fashioned quickly grew from a niche within the industry into the most common form of bicycling in the United States. The 1970s has been dubbed the decade of the "bike boom" by industry publications and by historians who have written on the subject. Many factors likely contributed to the increased number of bicycle riders and sales. Most explanations of the increase tend to emphasize the political, economic, and environmental concerns of adults and neglect the role that younger people played in the boom.